PENGARUH DIGITALISASI PELAYANAN PUBLIK, BUDAYA KERJA, DAN KOMPETENSI TERHADAP KINERJA PEGAWAI KECAMATAN GRATI KABUPATEN PASURUAN - Yayuk Desi Wahyuni,; Sundjoto, Sundjoto; Sri Rahayu , (Juremi: Jurnal Riset Ekonomi, 2025)
This study aims to analyze the influence of public service digitalization, work culture, and competence on employee performance. The research focuses on the Grati District Office in Pasuruan Regency, involving the entire population of 42 employees as respondents using a census method. A quantitative approach was adopted, with multiple linear regression analysis applied to examine the relationship between the independent variables (public service digitalization, work culture, and competence) and the dependent variable (employee performance). The results indicate that the implementation of digitalization has a significant impact on employee performance, as do work culture and competence. Simultaneously, these three independent variables significantly affect employee performance. These findings highlight the importance of digital transformation, the establishment of a positive work culture, and the development of individual competencies in enhancing the effectiveness of public sector organizations